(untitled) - Nickels, William G (New York, 2012)
Connect Business includes three features to help students prep, study, and apply the text content more effectively. Interactive Presentations for each chapter help students prep for class and bring the text to life. LearnSmart adaptive self-study technology provides students with a seamless combination of practice, assessment, and remediation for every concept in the textbook. And Interactive Applications stimulate critical thinking, reinforce key concepts, and ask students to apply business concepts to real world scenarios will help engage students beyond simple reading and recall.
Keywords: Industrial management,Business,Quản lý công nghiệp,Doanh nhân